Preparation and application of island-shaped nickel-vanadium-iron phosphide in-situ decoration nickel-vanadium-iron metal organic framework nanoflower / foamed nickel

By forming island-shaped nickel-vana ferrovana phosphide heterojunction on nickel-vana ferrovana metal organic frame nanoflower/foam nickel, the problems of low energy density of supercapacitors and insufficient stability of electrode materials are solved, high electrochemical performance and stability are achieved, and broad application prospects are broad.

CN119650320APending Publication Date: 2025-03-18HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411832126.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The low energy density of existing supercapacitors limits their large-scale application in portable electronic energy storage devices, and the electrode materials are insufficiently stable in alkaline environments.

Method used

The preparation method of in-situ decorative nickel-vana ferrous phosphide is adopted for the preparation of in-situ decorative nickel-vana ferrous metal organic frame nanoflower/foam nickel. The solvothermal method and in-situ partial phosphating method are used to form island-shaped heterojunctions, which enhance the stability of electrochemical reaction active sites and materials.

Benefits of technology

It improves the electrochemical performance and stability of supercapacitors, significantly improves specific capacity and conductivity, extends cycle life, and reduces the cost and environmental impact of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650320A_ABST
    Figure CN119650320A_ABST
Patent Text Reader

Abstract

The invention relates to synthesis of a novel nano material and application of the nano material in the field of supercapacitors, and discloses preparation and application of island-shaped nickel-vanadium-iron phosphide in-situ decoration nickel-vanadium-iron metal organic framework nano flower / foamed nickel. The invention aims to solve the problem that the existing super capacitor is insufficient in specific capacitance and energy density. The preparation method mainly comprises the following steps: 1, preparing nickel-vanadium-iron metal organic framework nanoflower / foamed nickel (NiVFe-MOF / NF) by a solvothermal method; and 2, preparing the heterojunction (NiVFe-P coated NiVFe-MOF / NF) of the nickel-vanadium-iron metal organic framework decorated by the island-shaped nickel-vanadium-iron phosphide (NiVFe-P) by an in-situ partial phosphorization method. The preparation method has the advantages of simplicity, low cost, high yield and the like. Due to the controllable heterojunction and abundant heterogeneous interfaces, the material shows excellent electrochemical characteristics. The specific capacitance is 2368.5 C g <-1 > when the specific capacitance is 1A g <-1 >, and the capacitance retention rate is still 90% after 10,000 cycles at the specific capacitance of 10A g <-1 >. In a two-electrode system, when the power density is 1.16 W kg <-1 >, the energy density of NiVFe-P-coated NiVFe-MOF / NF / / activated carbon / NF can reach 109.4 Wh kg <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of material preparation, electrochemistry and energy, and in particular to a method for preparing island-shaped nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflowers / nickel foam. Background Art

[0002] Supercapacitors play a key role in the new generation of portable electronic energy storage devices with their excellent power density, long cycle life and environmental protection characteristics. However, compared with lithium-ion batteries, the lower energy density limits the large-scale application of supercapacitors. It is generally believed that the performance of supercapacitors depends largely on the structure and composition of electrode materials. Therefore, it is urgent to develop new cathode materials with unique structures to improve the electrochemical performance of supercapacitors. Nickel-vanadium metal organic framework (NiV-MOF) has high electrochemical activity and specific capacity, showing great application potential in the field of supercapacitors. The NiV-MOF nanoflower structure not only has a large specific surface area and rich pore structure, which helps to fully expose the active sites, but also enhances the permeability of the electrolyte, thereby showing excellent electrocatalytic performance in electrolyzed water. In the application of supercapacitors, in addition to having excellent electrocatalytic activity, the electrode material must also be able to withstand OH in an alkaline environment. - Frequent embedding and de-embedding of ions to avoid structural damage and maintain its excellent stability. The nanoflower structure self-assembled from nanosheets has abundant open network space, which helps to alleviate volume expansion and reduce structural damage. Therefore, NiV-MOF nanoflowers have obvious advantages in improving the stability of supercapacitors; Trimetallic organic frameworks can significantly enhance the synergistic effect between different metal ions and optimize the electronic structure. Iron (Fe), as a transition metal widely distributed on the earth, is favored in the field of energy storage due to its low cost, low toxicity, rich oxidation states and excellent conductivity. Due to the similarity between Fe and Ni in coordination environment and atomic radius, Fe can partially replace Ni without changing the crystal structure. In addition, Fe can also adjust the interlayer spacing of nanosheets and promote the rapid diffusion of electrolyte ions. Therefore, Fe doping will significantly improve the specific capacity and conductivity of NiV-MOF; Heterostructures are generally considered to be a key way to improve the electrochemical performance of supercapacitors due to their unique electronic properties and interface effects. In particular, the in-situ formed island heterostructure can produce a pinning effect at the interface, limiting the lattice vibration of each component, and more effectively reducing the structural damage caused by lattice mismatch compared to traditional secondary growth or deposition methods. At the same time, this structure can also form a large number of heterogeneous interfaces, making full use of the synergistic effect of multiple components, promoting electron transfer, and enhancing reaction kinetics and specific capacity. Therefore, this is expected to further improve the stability and capacitance performance of NiV-MOF; In summary, we have successfully synthesized island-like nickel-vanadium-iron-phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflowers / nickel foam. Thanks to its island-like heterojunction with adjustable electronic properties and rich heterogeneous interfaces, the material exhibits excellent electrochemical performance and shows broad application prospects as a supercapacitor electrode material. Summary of the invention

[0003] The purpose of the present invention is to develop a metal organic framework-based heterogeneous material with excellent conductivity and stability to enhance the electrochemical performance of supercapacitors, and to propose a method for preparing an island nickel vanadium iron phosphide in-situ decorated nickel vanadium iron metal organic framework nanoflower / foam nickel electrode material.

[0004] The preparation method of the island-shaped nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam electrode material of the present invention is carried out according to the following steps: 1. Preparation of NiVFe-MOF / NF by solvothermal method The nickel foam was washed with anhydrous ethanol, acetone, 3 M hydrochloric acid and deionized water, respectively. Then 0.1-0.5 mmol NiCl2·6H2O, 0.1-0.4 mmol VCl3, 0-0.3 mmol FeCl3·6H2O and 0.3-1.0 mmol terephthalic acid were dissolved in a mixed solution of 25-50 mL N,N-dimethylformamide, 1-10 mL deionized water and 1-10 mL anhydrous ethanol. The above solution and nickel foam were transferred to a 100 mL autoclave and heated at 160°C for 12-48 h to obtain NiVFe-MOF / NF. 2. Preparation of NiVFe-P@NiVFe-MOF / NF heterojunction by in-situ partial phosphating method 0.5~2.0 g NaH2PO2·H2O and NiVFe-MOF / NF were placed in ceramic boats, which were placed in the upstream and downstream of the tube furnace, respectively, with a spacing of 8~15 cm between the two ceramic boats. Under Ar atmosphere, annealing was performed at 250~450°C for 2 h with a heating rate of 2°C / min to obtain NiVFe-P@NiVFe-MOF / NF heterojunction.

[0005] Compared with the existing technology, the present invention has the following beneficial effects: The island-shaped nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam supercapacitor electrode material prepared by the present invention comprises: first, the metal ion (Ni 2+ 、V 3+ and Fe 3+ ) and terephthalic acid ligands undergo repeated nucleation and dissolution processes in the solution. The uneven surface of nickel foam reduces the nucleation energy, so that the NiVFe-MOF nuclei preferentially attach to the surface of nickel foam to form nanosheets. Then, these nanosheets are intertwined and self-assembled to form nanoflowers. During the phosphating process, NiVFe-MOF / NF is used as a precursor and NaH2PO2 is used as a phosphorus source, which undergoes a disproportionate reaction during the annealing process to release PH3 and H2. With the introduction of PH3, some oxygen atoms connected to the metal center in NiVFe-MOF are pulled out, and phosphorus atoms penetrate into the bulk phase of NiVFe-MOF. Finally, island-shaped NiVFe-P is formed on the nanosheets of NiVFe-MOF nanoflowers, thereby obtaining a NiVFe-P@NiVFe-MOF heterojunction. The present invention has the advantages of low cost, environmental friendliness and controllable morphology.

[0006] The island-shaped nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam supercapacitor electrode material prepared by the present invention can form a large number of heterogeneous interfaces, which helps to increase the active sites of the electrochemical reaction and promote the rapid progress of the Faraday redox reaction; Fe doping and partial phosphating can significantly increase its electron density, reduce the barrier of ion diffusion, and accelerate OH - The adsorption process of nanoflowers and the pinning effect of heterogeneous interfaces can effectively alleviate the OH - The damage to the morphology and structure caused by frequent insertion and extraction of ions can effectively improve the stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 This is the microscopic morphology of the prepared island-like nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam; Figure 2 The crystal structure and chemical composition of the prepared island-like NiVFeP in-situ decorated NiVFe metal organic framework nanoflowers / nickel foam; Figure 3 The electrochemical performance of the prepared island-like NiVFeP in-situ decorated NiVFe metal organic framework nanoflowers / nickel foam in a three-electrode system; Figure 4The electrochemical performance of the hybrid supercapacitor assembled by in-situ decoration of nickel-vanadium-iron metal organic framework nanoflowers / nickel foam and activated carbon with island-like nickel-vanadium-iron phosphide prepared in a two-electrode system; Figure 5 This is the attached figure of the abstract, which is a scanning electron microscope photograph of island-like nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflowers / nickel foam. Specific implementation plan Specific implementation method 1: The preparation method of the island-shaped nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam supercapacitor electrode material is specifically carried out according to the following steps: Solvothermal preparation of NiVFe-MOF / NF The nickel foam was washed with anhydrous ethanol, acetone, 3 M hydrochloric acid and deionized water, respectively. Then 0.1-0.5 mmol NiCl2·6H2O, 0.1-0.4 mmol VCl3, 0-0.3 mmol FeCl3·6H2O and 0.3-1.0 mmol terephthalic acid were dissolved in a mixed solution of 25-50 mL N,N-dimethylformamide, 1-10 mL deionized water and 1-10 mL anhydrous ethanol to form a green solution. The above solution and nickel foam were transferred to a 100 mL autoclave and heated at 160°C for 12-48 h to obtain NiVFe-MOF nanoflowers / nickel foam; 2. Preparation of NiVFe-P@NiVFe-MOF / NF heterojunction by in-situ partial phosphating method 0.7~2.0 g NaH2PO2·H2O and NiVFe-MOF / NF were placed in ceramic boats, which were placed in the upstream and downstream of the tube furnace, respectively, with a spacing of 8~15 cm between the two ceramic boats. Under Ar atmosphere, annealing was performed at 300~450℃ for 2 h with a heating rate of 2°C / min to obtain NiVFe-P@NiVFe-MOF / NF heterojunction.

[0009] Specific implementation method 2: The preparation method of the island-shaped nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam supercapacitor electrode material is specifically carried out according to the following steps: The present embodiment differs from the specific embodiment 1 in that the reaction solution contains 0.04-0.06 mmol of FeCl3·6H2O in step 1. The rest is the same as the specific embodiment 1.

[0010] Specific implementation method three: The preparation method of the island-shaped nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam supercapacitor electrode material is specifically carried out according to the following steps: The present embodiment differs from the specific embodiments 1 and 2 in that 1.0-2.0 g of NaH2PO2·H2O is contained in the phosphating reaction in step 2. The rest is the same as the specific embodiments 1 and 2.

[0011] Specific implementation method 4: The preparation method of the island-shaped nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam supercapacitor electrode material is specifically carried out according to the following steps: The present embodiment differs from the specific embodiments 1 to 3 in that the phosphating temperature in the phosphating reaction in step 2 is 350-450° C. The rest is the same as the specific embodiments 1 to 3.

[0012] The following experiments were used to verify the effect of the present invention: The preparation method of the island-shaped nickel-vanadium-iron-phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam supercapacitor electrode material in this experiment is carried out according to the following steps: 1. Preparation of NiVFe-MOF / NF by solvothermal method The nickel foam was washed with anhydrous ethanol, acetone, 3 M hydrochloric acid and deionized water respectively. Then 0.4 mmol NiCl2·6H2O, 0.1 mmol VCl3, 0.15 mmol FeCl3·6H2O and 0.75 mmol terephthalic acid were dissolved in a mixed solution of 32 mL N,N-dimethylformamide, 2 mL deionized water and 2 mL anhydrous ethanol. The above solution and nickel foam were transferred to a 100 mL autoclave and heated at 160°C for 48 h to obtain NiVFe-MOF nanoflowers / nickel foam; 2. Preparation of NiVFe-P@NiVFe-MOF / NF heterojunction by in-situ partial phosphating method 1.0 g NaH2PO2·H2O and NiVFe-MOF / NF were placed in ceramic boats, which were placed in the upstream and downstream of the tube furnace, respectively, with a spacing of 8-15 cm between the two ceramic boats. Under Ar atmosphere, annealing was performed at 350°C for 2 h with a heating rate of 2°C / min to obtain NiVFe-P@NiVFe-MOF / NF heterojunction.

[0013] The present invention uses a three-electrode test system to study the electrochemical properties of the material, and uses the synthesized NiVFe-P@NiVFe-MOF / NF as the working electrode, Hg / HgO as the reference electrode, Pt as the control electrode, and 6 M potassium hydroxide solution as the electrolyte to test its electrochemical properties. In the two-electrode system, NiVFe-P@NiVFe-MOF / NF is used as the positive electrode, activated carbon / nickel foam (AC / nickel foam) is used as the negative electrode, and 6 M potassium hydroxide solution is used as the electrolyte to test its electrochemical properties.

[0014] Figure 1 The microscopic morphology of NiVFe-P@NiVFe-MOF / NF. NiV-MOF nanoflowers are evenly anchored on the surface of nickel foam ( Figure 1 ac), with good adhesion to nickel foam. These nanoflowers with a diameter of about 700 nm are composed of many ultrathin nanosheets. After Fe doping, NiVFe-MOF still maintains the same morphology and size as NiV-MOF. However, the nanosheets become thinner and the spacing between nanosheets increases significantly, which is conducive to the penetration of electrolytes ( Figure 1 d). After partial phosphating, NiVFe-P@NiVFe-MOF still maintains the flower-like morphology and size of NiVFe-MOF ( Figure 1 e). In addition, EDS results confirmed the presence and uniform distribution of Ni, V, Fe, P, O and C elements in NiVFe-P@NiVFe-MOF. In the transmission electron microscope image, NiVFe-MOF nanoflowers are composed of many nanosheets with a thickness of 2~3 nm ( Figure 1 gh). In addition, the nanosheets have a smooth surface ( Figure 1 i). After phosphating, NiVFe-P@NiVFe-MOF has a nanoflower morphology similar to that of NiVFe-MOF ( Figure 1 j). A large number of island-like heterojunctions are uniformly formed on the surface of the NiVFe-MOF smooth nanosheets ( Figure 1 k). High-resolution transmission images further reveal that these island heterojunctions are related to Ni, V, and Fe-based phosphides. d = 0.207 and 0.214 nm match the (112) and (321) crystal planes of Ni3P, respectively. d = 0.192 nm matches the (210) crystal plane of Fe2P. d = 0.185 and 0.187 nm match the (400) and (-113) crystal planes of VP2, respectively. Figure 1 l). This nanoflower island heterojunction is beneficial for exposing abundant heterointerfaces at the nanoscale and maximizing the contact area between metal active centers and electrolytes to enhance redox reaction capabilities.

[0015] Figure 2 The structure, chemical composition and valence state analysis of NiVFe-P@NiVFe-MOF. Figure 2In a), the diffraction peaks of NiV-MOF at 14.8°, 15.62°, 16.96°, 25.44°, 29.74°, 32.46°, 40.86°, and 43.36° correspond to the (001), (200), (400), (600), (-111), (311), (411), and (132) crystal planes of Ni-MOF (CCDC#985792), respectively. The diffraction peaks of NiVFe-MOF are the same as those of NiV-MOF, indicating that Fe doping does not change the crystal structure. In addition, these peaks show a slight shift to higher angles, and the peak intensity is reduced compared to NiV-MOF, indicating that Fe doping reduces the size of the original crystal structure. For NiV-P@NiV-MOF, peaks appear at 20.08°, 31.1°, 44.34°, 62.6°, and 76.36°, corresponding to the (200), (121), (112), (422), and (460) planes of Ni3P (PDF#89-4748), respectively. The peaks at 43.02° and 62.14° are attributed to the (003) and (-512) planes of VP2 (PDF#80-0990), respectively, in addition to the peaks at 14.8°, 15.9°, 17.32°, and 29.9° belonging to NiV-MOF. For NiVFe-P@NiVFe-MOF, two additional peaks appear at 25.8° and 36.14°, corresponding to the (001) and (200) planes of Fe2P (PDF#83-2337), respectively. In Fourier transform infrared spectroscopy ( Figure 2 b) NiV-MOF has a peak at 3592 and 3525 cm -1 The absorption bands at 1585 and 1369 cm-1 belong to the OH stretching vibration, which is related to hydroxyl groups and water molecules. -1 The peaks at 831 and 744 cm-1 correspond to the stretching vibration of the carboxyl group. -1 The two absorption bands on the left and right are attributed to the out-of-plane bending vibration of the C=CH bond in the benzene ring of PTA. -1 The peak belongs to the stretching vibration of the metal-oxygen bond. NiVFe-MOF has similar characteristic peaks to NiV-MOF, indicating that Fe atoms are successfully introduced into the NiV-MOF lattice, which is consistent with the XRD analysis results. NiV-P@NiV-MOF and NiVFe-P@NiVFe-MOF still retain the characteristic absorption peaks of the benzene ring, indicating that their precursor structures are retained during the phosphating process. In addition, the peaks at 552 and 423 cm -1 The absorption band of is weakened, indicating that part of the metal-oxygen bonds have been transformed into metal-phosphorus bonds, which reflects the successful synthesis of the heterostructure. Figure 2In c), NiV-MOF shows two strong peaks at 1438 and 1614 cm -1 , corresponding to the stretching vibrations of the C=O bond in -COOH and the C=C bond in the benzene ring. In addition, 1135 cm -1 The peak at 862 and 629.6 cm -1 The peak at 826 cm-1 may be related to the vibration mode of the benzene ring. The peak of NiVFe-MOF matches the vibration mode of NiV-MOF, further confirming that the two materials have similar structural features. Compared with NiV-MOF and NiVFe-MOF, the Raman peaks of NiVFe-MOF and NiVFe-P@NiVFe-MOF show a significant red shift, indicating that lattice distortion and defects are introduced after phosphating. In particular, the peak of NiVFe-P@NiVFe-MOF at 826 cm-1 is significantly red-shifted. -1 The peak intensity at is significantly higher than that of NiV-P@NiV-MOF, which indicates that Fe doping leads to an increase in the number of defects, which is beneficial to improving the electrochemical performance.

[0016] In X-ray photoelectron spectroscopy ( Figure 2 d), NiV-MOF shows peaks of Ni 2p, V 2p, C 1s, and O 1s. After Fe doping, characteristic peaks of Fe 2p appear in NiVFe-MOF. After phosphating, new P 2p peaks are observed in both NiV-P@NiV-MOF and NiVFe-P@NiVFe-MOF. In the high-resolution Ni 2p spectrum ( Figure 2 e) NiV-MOF exhibits two Ni 2p 3 / 2 and Ni 2p 1 / 2 The peak fitting further reveals that Ni exists in two oxidation states (Ni 2+ and Ni 3+ ) form. The two peaks in NiVFe-MOF shift to higher binding energy compared with NiV-MOF, indicating that Fe doping slightly changes its electronic structure. In addition, it can be clearly found that the two peaks further shift positively after phosphating. This shift can be attributed to the redistribution of electrons in the heterostructure. It is worth noting that Ni in NiV-P@NiV-MOF and NiVFe-P@NiVFe-MOF ᵟ+ The two new peaks at (853.1 and 870.3 eV) are attributed to the Ni-P bond, where Ni ᵟ+ represents the positively charged Ni group. In the high-resolution Fe 2p spectrum ( Figure 2 f) NiVFe-MOF shows Fe 2p 3 / 2 and Fe 2p 1 / 2The three spin-orbit splitting peaks correspond to different oxidation states of Fe, namely, Fe ᵟ+ , Fe 2+ and Fe 3+ In NiVFe-P@NiVFe-MOF, these peaks shift to higher binding energies, indicating that some electrons are transferred from Fe to P atoms during the phosphiding process, leading to the formation of new Fe-P chemical bonds. Figure 2 g), NiV-MOF can be decomposed into V 2p 3 / 2 and V 2p 1 / 2 Further peak fitting shows that V exists in multiple oxidation states (V 3+ 、V 4+ and V 5+ ). After Fe doping, V 2p 3 / 2 and V 2p 1 / 2 The peaks show a positive shift. Compared with pure NiV-MOF and NiVFe-MOF, the two peaks in the two heterostructures NiV-P@NiV-MOF and NiVFe-P@NiVFe-MOF show a significant negative shift, indicating that the electron affinity of V is enhanced after phosphating. Normally, the peaks associated with Fe and Ni move in the positive direction, while the peak associated with V moves in the negative direction. This phenomenon indicates that electron exchange occurs between Ni, V, and Fe, resulting in a change in the electronic structure. In the high-resolution O 1s spectrum ( Figure 2 h), the oxygen in the four materials exists in three forms, namely metal-oxygen, metal-hydroxyl and -OC=O bonds. The peak of NiVFe-P@NiVFe-MOF is located at the lowest binding energy position, indicating that Fe doping and phosphating promote electron transfer around oxygen. In the high-resolution P 2p spectrum ( Figure 2 In i), the peaks of NiV-P@NiV-MOF are located at 130.9 and 129.8 eV, corresponding to P2p 1 / 2 and P 2p 3 / 2 , which confirms the existence of metal-phosphorus bonds. The peak at 134.1 eV indicates the presence of high-valent phosphates on the surface of NiV-P@NiV-MOF, which is mainly due to partial oxidation of the material when exposed to air. However, the characteristic peaks of NiVFe-P@NiVFe-MOF shift to lower binding energies, further indicating that Fe doping adjusts the electronic structure at the heterointerface to enhance conductivity and reaction kinetics.

[0017] Figure 3 The electrochemical performance of NiVFe-P@NiVFe-MOF / NF in a three-electrode system is shown. In the cyclic voltammetry curve ( Figure 3 In a), all samples were charged at 100 mV s -1A pair of redox peaks are shown at the scan rate of , which are attributed to the Faradaic redox reaction. Obviously, NiVFe-P@NiVFe-MOF / NF has the largest enclosed area and the highest peak current density, indicating that it has the best capacitive characteristics. In the constant current charge-discharge curve ( Figure 3 b), all electrodes have charge-discharge plateaus, which are typical characteristics of battery-type materials. Obviously, NiVFe-P@NiVFe-MOF / NF has a high charge-discharge performance at 1 A g -1 The longest charge and discharge time is shown at a current density of , indicating that it has the highest specific capacity. Figure 3 c), each curve consists of an intercept on the x-axis, a semicircular arc in the high-frequency region, and a linear straight line in the low-frequency region, which correspond to the internal resistance (Rs), charge transfer impedance (Rct), and Warburg impedance (W) of the electrode material, respectively. NiVFe-P@NiVFe-MOF / NF shows the smallest material internal resistance (Rs is 0.37 Ω) and charge transfer impedance (Rct is 0.45 Ω), as well as the largest linear slope, which helps to overcome the dynamic limitations in the electrochemical process and improve the electron transfer efficiency and ion diffusion rate. In the curve of specific capacitance changing with current density ( Figure 3 d), the specific capacities of NiV-MOF, NiVFe-MOF, NiV-P@NiV-MOF, and NiVFe-P@NiVFe-MOF gradually decrease with increasing current density. -1 At a current density of 1.3 Å, the specific capacities of these four materials are 706.6, 1656, 1615, and 2368.5 C g, respectively. -1 In addition, NiVFe-P@NiVFe-MOF / NF exhibited a high thermal conductivity at 10 A g -1 It shows a rate performance of 71.9% at a current density of , which is significantly higher than other electrode materials.

[0018] The CV curves of NiVFe-P@NiVFe-MOF / NF at different scan rates are shown in Figure 2. Figure 3 As shown in e. Obviously, as the scan rate gradually increases, the cyclic voltammetry curve of NiVFe-P@NiVFe-MOF / NF still maintains good symmetry, which indicates that NiVFe-P@NiVFe-MOF / NF has a good dynamic response with KOH electrolyte. The reaction kinetics and charge storage mechanism of NiVFe-P@NiVFe-MOF / NF were further studied based on the cyclic voltammetry curve. The b values ​​of the anode and cathode peaks are close to 0.55 and 0.52, indicating that the charge storage is mainly derived from diffusion control ( Figure 3 f). The total charge accumulation can be divided into two parts: capacitance control and diffusion control. -1At a scan rate of , the capacitance contribution of NiVFe-P@NiVFe-MOF / NF is 44% ( Figure 3 g). In addition, the contribution of capacitance control increases from 44% to 93% with increasing scan rate. The constant current charge-discharge curves of NiVFe-P@NiVFe-MOF / NF have good symmetry, and the charge-discharge time decreases with increasing current density, indicating good reversibility and small energy loss during the charge-discharge process ( Figure 3 i). at 10 A g -1 Under the same test conditions, the capacity retention rate of NiVFe-MOF / NF after 10,000 cycles is only 77.3%. However, under the same test conditions, the capacity retention rate of NiVFe-P@NiVFe-MOF / NF can reach 90%, which shows its excellent cycle stability and outstanding electrochemical reversibility; the similar curves of NiVFe-P@NiVFe-MOF / NF in the first 10 and the last 10 cycles further indicate its good stability and cycle life ( Figure 3 j).

[0019] Figure 4 The electrochemical performance of NiVFe-P@NiVFe-MOF / NF / / AC / NF in a two-electrode system is shown in the figure. The assembly diagram of NiVFe-P@NiVFe-MOF / NF / / AC / NF hybrid supercapacitor is shown in the figure. Figure 4 As shown in a. During the charging process, OH in the electrolyte - Move to NiVFe-P@NiVFe-MOF / NF and react with metal ions for oxidation. The discharge process is the opposite of the above process. The voltage window of NiVFe-P@NiVFe-MOF / NF / / AC / NF is determined by the CV curves of the positive and negative electrodes ( Figure 4 b). AC / NF shows electric double layer capacitance in the voltage range of -1.0-0 V, and NiVFe-P@NiVFe-MOF / NF shows battery-type redox reaction in the voltage range of -0.3-0.7 V, indicating that the theoretical voltage window of NiVFe-P@NiVFe-MOF / NF / / AC / NF is 0-1.7 V. For further verification, cyclic voltammetry tests were performed in different voltage ranges ( Figure 4 c). When the voltage exceeds 1.7 V, the curve shows obvious polarization. Under different voltage windows, the constant current charge-discharge curves of NiVFe-P@NiVFe-MOF / NF / / AC / NF have no obvious charging platform and maintain good symmetry ( Figure 4d). Therefore, we selected the voltage range of 0-1.7 V to further study the electrochemical performance of NiVFe-P@NiVFe-MOF / NF / / AC / NF. The cyclic voltammetry curve of NiVFe-P@NiVFe-MOF / NF / / AC / NF has obvious redox peaks, and its shape does not change with the increase of scan rate (5-100 mV s -1 )( Figure 4 e). The b values ​​corresponding to the redox peaks are 0.77 and 0.79, respectively, indicating that the assembled NiVFe-P@NiVFe-MOF / NF / / AC / NF fully utilizes the synergistic effect between capacitor-type and battery-type electrode materials ( Figure 4 f). In order to understand the contribution of the capacitive and battery types in the electrochemical process, we measured the contribution ratio of these two parts at different scan rates. -1 When the capacitance is controlled at 32.39%, the diffusion is controlled at 67.61% ( Figure 4 g). With the increase of scan rate, the proportion of diffusion control decreases (67.61%~9.18%) and the proportion of capacitance control increases (32.39%~90.82%). It can be clearly seen from these results that the two electrodes synergistically participate in charge storage to expand the potential window and improve the specific capacity. The nonlinearity of the constant current charge-discharge curves reveals the contribution of the two electrodes in the electrochemical process. In addition, the almost symmetrical curves show that NiVFe-P@NiVFe-MOF / NF / / AC / NF has a good Coulombic efficiency ( Figure 4 i). NiVFe-P@NiVFe-MOF / NF / / AC / NF at 1 A g -1 It can reach 338.9 C g -1 When the power density is 1.16 kW kg -1 The energy density of NiVFe-P@NiVFe-MOF / NF / / AC / NF can reach 109.4 Wh kg -1 ( Figure 4 j). At 10 A g -1 After 10,000 cycles under the same conditions, the capacity retention rate of NiVFe-P@NiVFe-MOF / NF / / AC / NF was 93.4% ( Figure 4 k), indicating that it has good reversibility and cycle stability. The obtained electrode materials are assembled into button batteries, and two button batteries are connected in series to power LEDs and stopwatches, which can enable the LEDs and stopwatches to work stably for a long time (such as Figure 4 k). The above results show that in situ embedding of NiVFe-P on NiVFe-MOF nanoflowers to construct island heterojunctions can greatly improve the capacity and stability of SCs, providing broad application potential in the field of energy storage.

[0020] Figure 5 This is a scanning electron microscope photo of island-like nickel-vanadium-iron phosphide in situ decorated nickel-vanadium-iron metal organic framework nanoflowers / nickel foam.

Claims

1. Preparation and application of island-like nickel-vanadium-iron phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflowers / nickel foam, characterized in that The preparation method of island-like nickel-vanadium-iron-phosphide in-situ decorated nickel-vanadium-iron metal organic framework nanoflower / nickel foam as supercapacitor electrode material is carried out according to the following steps:

1. Preparation of NiVFe-MOF / NF by solvothermal method The nickel foam was washed with anhydrous ethanol, acetone, 3 M hydrochloric acid and deionized water, respectively. Then 0.1-0.5 mmol NiCl2·6H2O, 0.1-0.4 mmol VCl3, 0-0.3 mmol FeCl3·6H2O and 0.3-1.0 mmol terephthalic acid were dissolved in a mixed solution of 25-50 mL N,N-dimethylformamide, 1-10 mL deionized water and 1-10 mL anhydrous ethanol. The above solution and nickel foam were transferred to a 100 mL autoclave and heated at 160°C for 12-48 h to obtain NiVFe-MOF / NF.

2. Preparation of NiVFe-P@NiVFe-MOF / NF heterojunction by in-situ partial phosphating method 0.5~2.0 g NaH2PO2·H2O and NiVFe-MOF / NF were placed in ceramic boats, which were placed in the upstream and downstream of the tube furnace, respectively, with a spacing of 8~15 cm between the two ceramic boats. Under Ar atmosphere, annealing was performed at 250~450°C for 2 h with a heating rate of 2°C / min to obtain NiVFe-P@NiVFe-MOF / NF heterojunction.

2. The preparation method according to claim 1, characterized in that The content of VCl3 in step 1 is 0.1-0.4 mmol.

3. The preparation method according to claim 1, characterized in that: The content of FeCl3·6H2O in step 1 is 0-0.3 mmol.

4. The preparation method according to claim 1, characterized in that: The content of NaH2PO2·H2O in step 2 is 0.5-1.5 g.

5. The preparation method according to claim 1, characterized in that: The annealing temperature in step 2 is 300-450°C.

Citation Information

Cited By

  • Quaternary transition metal oxide, electrode and preparation method and application thereof

    CN122380457A